A programme to foster resilience among kindergarten children - Erdei Róbert (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2024)
Abstract. In this study, I will briefly introduce a development programme designed for preschool children to foster resilience, flexible coping, and facing risk factors that may threaten their optimal development at this age. Resilience is the ability to adapt and bounce back from difficult life experiences or challenges. Children must develop resilience early to help them cope with challenges and stress.
Keywords: resilience; kindergarten children